Antecedents to successful adoption of e-procurement in textile and apparel firms in Kenya - Arasa, Robert (My University, 2012)
This study examined the factors that affect implementation of e-procurement within the textile and apparel firms in Kenya. Specifically it sought to investigate the effect of organizational issues, environmental factors and technological factors on the implementation of e-Procurement. A survey approach was employed, using a stratified random sampling to ensure representativeness Both quantitative and qualitative methods of data analysis were used. Descriptive statistics as well as regression analysis were used to facilitate examination of the relationship between the variables of interest. The study findings indicate that environmental factors have the most influence on e-procurement implementation, followed by technological and organizational factors respectively. The study points out that management support, employee empowerment, policy strengthening in ICT use are key to effective e-procurement implementation and therefore should be given due attention.
Keywords: E-procurement; Implementation; Organizational factors; Environmental factors; Technological factors